Breast Cancer, On Call - Perez-Lirio, MD, Gracia (North American Journal of Medicine and Science, 2009)
A physician’s workday can hardly be called typical. Other than busy and hectic, it is always unpredictable. Being on call is a time when one is expected to be available twenty four hours. Patients, nurses, pharmacists call on-demand with questions, problems and concerns. But one call I was never prepared to receive was about my own breast cancer diagnosis.